2019
DOI: 10.1021/acsmacrolett.9b00713
|View full text |Cite
|
Sign up to set email alerts
|

Multicompartment Microparticles with Patchy Topography through Solvent-Adsorption Annealing

Abstract: We report on the evaporation-induced confinement assembly (EICA) of polystyrene-b-polybutadiene-b-poly­(methyl methacrylate) (PS-b-PB-b-PMMA, SBM) triblock terpolymers into multicompartment microparticles and follow their morphological evolution during solvent-adsorption annealing. We initially obtain elliptic microparticles with axially stacked PS/PB/PMMA morphology using cetyltrimethylammonium bromide (CTAB) as surfactant. Exchanging the surfactant to poly­(vinyl alcohol) (PVA) during solvent vapor annealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 47 publications
(82 reference statements)
0
40
0
Order By: Relevance
“…The BCP particles were generated through solvent-evaporative chloroform-in-water emulsions. [42,[48][49][50][51][52][53][54][55] In brief, poly(styrene-block-dimethylsiloxane) (PS-b-PDMS, number-average molecular weight (M n ) = 33 kg mol -1 ) BCP particles containing poly(styrene-random-poly vinylbenzylazide) (P(S-r-N 3 ), M n = 2 kg mol -1 ) polymers were generated. The use of SPG membrane emulsification affords the generation of uniformly-sized BCP particles (size ≈ 950 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The BCP particles were generated through solvent-evaporative chloroform-in-water emulsions. [42,[48][49][50][51][52][53][54][55] In brief, poly(styrene-block-dimethylsiloxane) (PS-b-PDMS, number-average molecular weight (M n ) = 33 kg mol -1 ) BCP particles containing poly(styrene-random-poly vinylbenzylazide) (P(S-r-N 3 ), M n = 2 kg mol -1 ) polymers were generated. The use of SPG membrane emulsification affords the generation of uniformly-sized BCP particles (size ≈ 950 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The PS, PB and PMMA microphases alternate in form of an axially stacked lamellar structure due to their equal‐sized block compositions (S 32 B 40 M 28 202K ) as well as the comparable affinity for PS ( δ =18.5 MPa 1/2 ) and PMMA ( δ =19.0 MPa 1/2 ) to the SDS/water interface [42] . In TEM (Figure 1 d–f), the three microphases can be clearly identified: PS appears grey, PB dark due to osmium tetroxide (OsO 4 ) staining, and PMMA bright; the PMMA lamella appears thinner in TEM due to its degradation under the e ‐beam [43] . Grey scale analysis (Figure S3) revealed that the lamella thickness ( T = L 0 /2, Table 1) were 0.037 μm, 0.049 μm, and 0.052 μm for d pore =0.3 μm, 0.8 μm, and 2.0 μm, respectively.…”
Section: Figurementioning
confidence: 91%
“…[42] In TEM (Figure 1 d-f), the three microphases can be clearly identified: PS appears grey, PB dark due to osmium tetroxide (OsO 4 ) staining, and PMMA bright; the PMMA lamella appears thinner in TEM due to its degradation under the ebeam. [43] Grey scale analysis (Figure S3) revealed that the lamella thickness (T = L 0 /2, Table 1) were 0.037 mm, 0.049 mm, and 0.052 mm for d pore = 0.3 mm, 0.8 mm, and 2.0 mm, respectively. It is reasonable that the lamella thickness increased with larger membrane pore diameter.…”
Section: Kmentioning
confidence: 99%
“…For example, a mixture of CTAB and poly(vinyl alcohol) (PVA) provides a neutral interaction for PS- b -PI- b -P2VP triBCPs (PI: polyisoprene), affording the formation of prolate shape [ 43 ]. Confinement assembly of ABC triblock terpolymers has been further reported by varying the type of each block: PS- b -PB- b -PMMA, PS- b -PB- b -PtBMA, and PS- b -P4VP- b -PtBMA (PMMA: poly(methyl methacrylate), PtBMA: poly(t-butyl methacrylate)) [ 44 , 51 ]. Under spherical confinement stabilized by CTAB, the PS- b -PB- b -PtBMA triblock terpolymer adopts a hemispherical shape with a mixture of concentric lamella–axial lamella morphology [ 44 ].…”
Section: 3d-confined Assembly Of Bcps In Emulsionmentioning
confidence: 99%